Design Concept of Airboat Based Water Hyacinth Cutting Vessel - Adullah, Kharis; Sumardiono; Herijono, Boedi (Universitas Pendidikan Ganesha, 2025)
Water hyacinth (Eichhornia crassipes) is a fast-growing aquatic plant, floats on the surface of the water and is often considered a weed because it can cover the water surface, inhibit photosynthesis, reduce oxygen levels, clog airways, and disrupt human activities such as fishing, transportation, and irrigation. Therefore, an effective tool is needed to clean waters filled with water hyacinth. This study aims to design a water hyacinth cutting tool concept based on an airboat. In this study, a master design approach method is used to obtain an airboat design quickly and efficiently. The research subjects involved are the airboat structure design, including the hull shape and propulsion system, and ship stability calculations. The data collection method in this study involves a literature study of previous technical references, empirical data from similar ships, and the technical parameters of the engine and hull structure. Data analysis was carried out using marine engineering calculation methods. The study results show that the resulting airboat design meets the stability criteria according to IMO (International Maritime Organization) standards, and general arrangements can be produced quickly. Through this research, we can create innovative and applicable solutions to the water hyacinth problem, which often disrupts irrigation activities, water transportation, and tourism.